2015
DOI: 10.1186/s12864-015-1498-0
|View full text |Cite
|
Sign up to set email alerts
|

Plastome organization and evolution of chloroplast genes in Cardamine species adapted to contrasting habitats

Abstract: BackgroundPlastid genomes, also known as plastomes, are shaped by the selective forces acting on the fundamental cellular functions they code for and thus they are expected to preserve signatures of the adaptive path undertaken by different plant species during evolution. To identify molecular signatures of positive selection associated to adaptation to contrasting ecological niches, we sequenced with Solexa technology the plastomes of two congeneric Brassicaceae species with different habitat preference, Card… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
85
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 92 publications
(91 citation statements)
references
References 90 publications
5
85
0
Order By: Relevance
“…The gene ycf 1 was crossed at the junction of IRb/SSC and SSC/IRa, leading to incomplete duplication of the protein-coding gene within IRs (Figure 1). The overall GC contents of cpDNA ranged from 36.28 to 36.35% (Table 1), suggesting that the AT-rich contents of this genus are similar to other Brassicaceae plastid genomes sequenced so far (Hu S. L. et al, 2015). In general, the genome features of six species were found to be quite similar in gene content, gene order, introns, intergenic spacers, and AT content.…”
Section: Resultssupporting
confidence: 61%
“…The gene ycf 1 was crossed at the junction of IRb/SSC and SSC/IRa, leading to incomplete duplication of the protein-coding gene within IRs (Figure 1). The overall GC contents of cpDNA ranged from 36.28 to 36.35% (Table 1), suggesting that the AT-rich contents of this genus are similar to other Brassicaceae plastid genomes sequenced so far (Hu S. L. et al, 2015). In general, the genome features of six species were found to be quite similar in gene content, gene order, introns, intergenic spacers, and AT content.…”
Section: Resultssupporting
confidence: 61%
“…Several regions highlighted as hyper or moderately variable regarding the nucleotide diversity values across Opuntioideae chloroplast sequences (i.e., accD, ycf1, clpP, petD, rpl32 and ccsA) have been reported to be putatively under positive selection in some lineages, such as Brassicaceae, Bignoniaceae, Rutaceae, Orchidaceae, Geraniaceae and Poaceae (Hu et al 2015;Weng et al 2016;Dong et al 2018;Carbonell-Caballero et al 2015;Ruhlman and Jansen 2018;Thode & Lohmann 2019;Park et al 2017;Piot et al 2018). Positive selection may come into play in response to environmental changes (Piot et al 2018).…”
Section: Insights From Chloroplast Genome Assemblies In Opuntioideae mentioning
confidence: 99%
“…For example, the accD gene, which encodes the β -carboxyl transferase subunit of acetyl-CoA carboxylase, is an essential and required component for plant leaf development (Kode et al 200), and it is suggested to have played a pivotal role in the adaptive evolution of orchids (Dong et al 2018). The signatures of positive selection under accD gene observed in Brassicaceae and Campanulaceae have also indicated that this gene may have been repeatedly involved in the adaption to specific ecological niches during the radiation of eudicotyledonous plants (Rousseau-Gueutin et al 2013;Hu et al 2015). Considering the harsh environment that cacti display their fitness already expressed in its peculiar morphology and physiology, further studies should be carried to investigate the putative relation of chloroplast rearrangement -such as pseudogenization, loss of genes, translocation and inversion -with ecological features.…”
Section: Insights From Chloroplast Genome Assemblies In Opuntioideae mentioning
confidence: 99%
“…In contrast, ycf1 is exceptionally divergent across land plants (Dong et al 2015) and shows elevated ω in some angiosperm lineages (e.g. Hu et al 2015). Surprisingly, ycf1…”
Section: Selection On Picea Plastid Genesmentioning
confidence: 99%